The Importance of Creativity and Innovation in Maintaining Business in the Pandemic Situation: A Case Study of Micro Small and Medium Enterprises (MSME) Managed by Millennial Groups in Jakarta - Baby Poernomo; Anita Maulina; Anisa Arizona Bandi; Jana Sandra; Muhammad Sholeh (Budapest International Research and Critics University, 2021)
This research is aiming at answering the questions of what problems experienced by millennial MSMEs during the pandemic situation and how millennial MSMEs optimize their creativity to produce innovations in order to survive in the pandemic era. This research applies a case study approach from qualitative research design. In this study a semi-structured interview is conducted to 6 MSMEs which are managed by millennial entrepreneurs, consist of food and beverage business, fashion and training services. The research proved that MSMEs managed by millennial show high creativity and innovation so that their business can continue to run in the midst of pandemic, even it continues to show progress in a wider reach area to different provinces. In addition, the results of this study can be used as input for MSMEs in Indonesia to be more creative in order to lead to innovation.